Enhanced thermopower in flexible tellurium nanowire films doped using single-walled carbon nanotubes with a rationally designed work function - Choi, Jaeyoo; Lee, Kunsil; Park, Chong Rae; Kim, Heesuk (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
As commercial interest in flexible power-conversion devices increases, the demand is growing for high-performance alternatives to brittle inorganic thermoelectric materials. As an alternative, we propose a flexible single-walled carbon nanotube (SWCNT)-doped tellurium nanowire (TeNW) hybrid film and, for the first time, rationally engineer the work function of the SWCNTs to effectively filter charge carriers in an energy-dependent manner at the interfaces between the carbon and the inorganic semiconductor. The acid treatment used to control the SWCNT work function allows the interfacial barrier between the SWCNT and the TeNW to be raised and lowered. While the hybrid film with a large barrier of 0.82 eV has a low power factor due to poor carrier transfer, the power factor (3.40 mu W m(-1) K-2) in the film with a lower barrier of 0.23 eV is several times higher than that of either pure TeNW or hybrid film with 0.82 eV due to effective energy filtering effect. The transport characteristics of the hybrid film are explored to quantitatively elucidate the carrier filtering at the SWCNT-TeNW interfaces. These demonstrate the effectiveness of optimizing SWCNT work functions to improve the thermoelectric properties of SWCNT/TeNW hybrid films, thus indicating that this strategy can be applied to flexible/or wearable thermoelectrics. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: THERMOELECTRIC PROPERTIES; POLYMER NANOCOMPOSITES; ORGANIC COMPOSITES; POWER; POLY(3,4-ETHYLENEDIOXYTHIOPHENE); NANOSTRUCTURES; INTERFACE; BEHAVIOR; FABRICS; FIGURE